Kako naj zveni mesto? - Kovačič, Mojca (Etnolog. Nova vrsta (Ljubljana), 2018)
The article addresses church bell ringing and street music in Ljubljana. After a brief introductory presentation of the general research concepts concerning sound and soundscape, which are used by the research community, the article describes the contemporary attitude of urban and environmental policies to sound in the public space, and how they include them in the concept of the quality of living. On the other hand, the author describes the response of people to church bell ringing and street music, revealing a dichotomy between the institutional treatment of sound in the town and the experience and perception of sounds by the town's inhabitants.
Keywords: cerkveni zvonovi; church bells; cities and towns; hrup; Ljubljana; Ljubljana (Slovenia); mesta; noise; perception; predpisi; regulations; sound; street music; ulična glasba; zaznavanje; zvok